2014
DOI: 10.4103/1008-682x.122583
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal/permeability-increasing protein originates in both the testis and the epididymis and localizes in mouse spermatozoa

Abstract: Bactericidal/permeability–increasing protein (BPI) is an endogenous antibiotic protein with activity against gram–negative bacteria. In the present study, we examined the expression of BPI in postnatal mouse testes and epididymides as well as the subcellular localization within epididymal spermatozoa. Our results showed that, BPI mRNA was expressed in testis and epididymis independently. Throughout the epididymis, the BPI protein level gradually decreased in the epididymal epithelium in a spatial manner, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The bactericidal/permeability-increasing (BPI) protein is an endogenous protein with antimicrobial properties ( Zhou et al, 2013 , 2014 ) which acts as a super-antibiotic due to its endotoxin-neutralizing activity ( Luo et al, 2012 ; Qin et al, 2017 ). Compelling evidence has highlighted a strong link between BPI and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The bactericidal/permeability-increasing (BPI) protein is an endogenous protein with antimicrobial properties ( Zhou et al, 2013 , 2014 ) which acts as a super-antibiotic due to its endotoxin-neutralizing activity ( Luo et al, 2012 ; Qin et al, 2017 ). Compelling evidence has highlighted a strong link between BPI and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, it is produced by neutrophils and the epithelial lining of mucosa as part of an antimicrobial defense mechanism (Schultz and Weiss, 2007). Proteins encoded by BPI and the BPI-like PLUNC genes from the same superfamily, have been found in the seminal plasma of rams (Soleilhavoup et al, 2014;van Tilburg et al, 2020), and the spermatozoa membrane of mice (Zhou et al, 2014) and rodents (Yano et al, 2010), and are hypothesized to have a role in the sperm-oocyte fusion process (Li et al, 2013). Even if BPI were to be identified in the semen of bulls, the finding in the embryos of the present study is likely not a direct result of paternal transcripts deposited to the oocyte at fertilization, since these transcripts start to degrade at EGA and should not be abundant in the analyses of embryonic gene expression at the blastocysts stage (Graf et al, 2014;Jiang et al, 2014).…”
Section: Other Transcriptsmentioning
confidence: 99%
“…In the male murine reproductive system, BPI was reported to be selectively expressed in testes and in the epididymis, not in the seminal vesicles, prostate, or solidification glands [ 50 ]. In our colleagues′ previous study, they discovered that mouse BPI is secreted by the epididymal epithelium and then localized to the surface of the sperm plasma membrane [ 51 ]. BPI is not expressed in the organs closer to the external environment; this finding suggests that BPI may have multiple functions in the male reproductive system not only the antimicrobial function in other organs.…”
Section: Bactericidal/permeability-increasing Protein (Bpi) Is a Novementioning
confidence: 99%
“…BPI is not expressed in the organs closer to the external environment; this finding suggests that BPI may have multiple functions in the male reproductive system not only the antimicrobial function in other organs. Furthermore, they found that BPI is enriched in the equatorial segment [ 51 ]. Thus, our colleagues and we are interested in the function of BPI in male infertility.…”
Section: Bactericidal/permeability-increasing Protein (Bpi) Is a Novementioning
confidence: 99%